Dog Heroes : A Nonfiction Companion to Dogs in the Dead of Night - Osborne, Mary Pope and Boyce, Natalie Pope (New York Random House, 2011)
Answers questions about the history and behavior of dogs and provides true stories of dog heroics
Inlclude Illustration and Index
Keywords: Working dogs -- Animal heroes